PROBLEMATIKA PELAKSANAAN KURIKULUM 2013 PADA PROSES PEMBELAJARAN BIOLOGI KELAS VII SMP DI KECAMATAN RAMBAH HILIR - Nurul Afifah, Darmin Sayuti, Pramono (FKIP UMSB, 2017)
This research purposed on knowing the set of problems on curriculum 2013 implementation in biology learning process in VIIth grade junior high school in Rambah Hilir subdistrict. This research has been done from July until December 2015. The method that has been use is descriptive qualitative with questionnaire. Populations and samples of this research are 6 teachers from 11 schools. The result of this research gained from questionnaire data analysis with 87,97% average percentage with very good criteria. The set of problems the VIIth grade junior high school teachers in Rambah Hilir subdistrict deal with on curriculum 2013 implementation in biology learning process are availability of books and supporting infrastructure that not quite enough, very short in time coaching, limited media utilizing and the very hard appraisal that also needs a lot of time. Key Word: descriptive qualitative, curriculum 2013, The set of problems